Necessidades de pessoas com Síndrome de Down: análise psicológica para desenvolvimento de jogo com tecnologia Kinect - Nayana Tallita Pereira Julho (Universidade Federal do Amazonas, 2016)
Throughout the time, the Down syndrome has been perceived in different ways, depending on the evolution of thought and the historical-cultural context, expressed in each era. Having been linked to sin when the prevailing religious view on the knowledge produced and characterized only by their phenotype while science was still crawling on the path to real discovery, it is now known that when speaking of Down syndrome, speech refers to a genetic condition resulting from the presence of extra material from chromosome 21 in the genetic composition of the individual. It is known that Down syndrome is the most frequent cause of mental retardation in the world population, and the study of genetic imbalance eliminates any idea of guilt that may be from parents with lack of information. Furthermore, research within this theme contribute to the development of treatments to be made available to the bearer, aimed at development and a better quality of life for these people. By requesting a consultancy for the development of the game with kinect technology that works as an aid in the treatment of Down syndrome therapy, there was extensive research and qualitative analysis of technical and scientific material about this genetic condition, from which recognize the characteristics, needs, difficulties, capabilities and potential of the carriers; aspects from which it was possible to draw up suggestions for characters, settings, contexts and behaviors to be supplied and encouraged by the tool. There was the highlight of the difficulties and needs in matters mainly related to motor development, learning, 6 communication and educational inclusion of patients with the syndrome. It is noted that the idea formulated for the development of therapy does not seek to replace other forms of assistance, but aid through a joint effort in treatment of patients with Down syndrome. Indicates the need for analysis of the construction and testing of the game enhancements are made so that the tool.